KARAKTERISTIK TANAH DASAR KOLAM PODSOLIK MERAH KUNING MENURUT PENGELOMPOKAN UMUR DENGAN PEMBERIAN KAPUR CaCO3 - Saberina Hasibuan; Syafriadiman Syafriadiman; Tardilus Tardilus; Edi Putra (DINAMIKA PERTANIAN, 2016)
This study aims to investigate the characteristics of pond bottom PMK according to the age grouping, quality improvement PMK and water quality of lime CaCO3. Research use two methods: the first, randomized block design with three replications, which is one factor CaCO3 lime, lime dosage of five level i.e. (g/m2) and the 2 age groups pond (year). Determination of the dose of lime in pond bottom soil and age class texture, and new pond (<4 years) and old (> 5-10 years). The second, addition of lime to the soil pH neutral RYP using completely randomized design with three replications, ie at an age (years) (O1) 0-5; (O2) 6-10; (O3) 11-15; (O4) 16-20. The results showed that the lime requirement CaCO3, showed dose of lime significant effect on the characteristics of soil pH, organic matter content, and CEC, otherwise the water quality parameters, namely hardness and dissolved oxygen. Age pond is also an influence on soil chemical parameters namely pH, and water chemistry parameters is dissolved oxygen. Effect of treatment was highest in 168.00 g CaCO3/m2 on the soil pH, and dissolved oxygen in the water in a pond of new and old, as well as organic matter content and water hardness for the new pond, while treatment 112,00g CaCO3/m2 on the hardness of the water for a long pond. Determination of the lime requirement CaCO3 in second method shows how 53,21g CaCO3/m2 tend to improve soil quality by increasing the life of the pond. Effect of lime CaCO3 against organic matter content pond increased with increasing an age of pond. YRP pond bottom soil characteristics and quality of the pond water increases with lime CaCO3.